Density Functional Theory Study on the Electronic Structures of Oxadiazole Based Dyes as Photosensitizer for Dye Sensitized Solar Cells - Umer Mehmood; Ibnelwaleed A. Hussein; Khalil Harrabi; Shakeel Ahmed (Advances in Materials Science and Engineering)
The molecular structures and UV-visible absorption spectra of complex photosensitizers comprising oxadiazole isomers as the π-bridges were analyzed by density functional theory (DFT) and time-dependent DFT. The ground state and excited state oxidation potentials, HOMOs and LUMOs energy levels, and electron injection from the dyes to semiconductor TiO2 have been computed in vacuum here. The results show that all of the dyes may potentially be good photosensitizers in DSSC. To justify the simulation basis, N3 dye was also simulated under the similar conditions. Simulated absorption spectrum, HOMO, LUMO, and band gap values of N3 were compared with the experimental values. We also computed the electronic structure properties and absorption spectra of dye/(TiO2)8 systems to elucidate the electron injection efficiency at the interface. This work is expected to give proper orientation for experimental synthesis.